Kepemimpinan Adaptif dan Kelincahan Organisasi di Era Transformasi Digital: Tinjauan Literatur - Erlangga Rahimi; Mulyadi Muchtiar; Ahmad Budi Sulistioyuwono; Rahma Wahdiniwaty; Deden Abdul Wahab Sya`roni (Pusat Riset dan Inovasi Nasional, 2026)
Digital transformation has driven significant changes in organizational management systems, thus demanding adaptive leadership and organizational agility as a key prerequisite for surviving in a dynamic environment. This study aims to analyze the relationship between adaptive leadership and organizational agility in the context of digital transformation through the Systematic Literature Review (SLR) approach. Data were obtained from accredited national journals and relevant international literature, then analyzed using thematic analysis techniques to identify patterns of relationships between variables. The results of the study show that adaptive leadership plays an important role in increasing organizational agility indirectly through strengthening organizational learning and dynamic capabilities. Organizational learning serves as the main mechanism that allows organizations to adapt through the continuous learning process, while dynamic capabilities are the link in transforming learning into strategic responses. Digital transformation accelerates the need for organizations to have a high level of agility in the face of change. In conclusion, organizational agility is the result of systemic processes influenced by adaptive leadership, organizational learning, and dynamic capabilities. This study makes a theoretical contribution to the development of the literature on leadership and strategic management in the digital age as well as practical implications for organizations in improving adaptability to the ever-changing environment.